Gender Innovation and Migration in Switzerland - Falk, Francesca (Palgrave Studies in Migration History, 2019)
This open access book analyses migration and its relation to socio-political transformation in Switzerland. It addresses how migration has made new forms of life possible and shows how this process generated gender innovation in different fields: the changing division of work, the establishment of a nursery infrastructure, access to higher education for women, and the struggle for female suffrage. Seeing society through the lens of migration alters the perspective from which our past and thus our present is told-and our future imagined.